2017
DOI: 10.1080/1547691x.2016.1249985
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arsenic on porcine dendritic cells in vitro

Abstract: Exposure to arsenic (As) is an ongoing, and in some places increasing, health problem. Still, however, the effects of As exposure on the immune system are not well understood. Dendritic cells (DC) are a critical immune cell that bridges the innate and adaptive immune systems. To determine the impact of inorganic (i)As exposure on DC, the effects of (geo)anthropogenically relevant levels of NaAsO 2 on the function of porcine monocyte-derived DC (MoDC) were evaluated in an in vitro model. The results showed a lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…For instance, in 2012, Morzadec et al have shown inhibitory activity of As­(III) on IL-17A expression of T H 17 cells. , In addition to the effect on T cells, environmental ATO was demonstrated to affect macrophage maturation by disruption of cytoskeletal and phagocytic processes as well as deranged surface marker and cytokine expression (downregulation of CD11b, upregulation of the TLR4 coreceptor CD14, as well as of TNF-α and IL-8). , Contradicting these data, a study on inhaled ATO performed in mice demonstrated no impact on innate immune cell status, however, impaired humoral responses . Furthermore, a DC-depleting effect of As has been described in a porcine in vitro model …”
Section: Immunological Effects Of Specific Metal Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, in 2012, Morzadec et al have shown inhibitory activity of As­(III) on IL-17A expression of T H 17 cells. , In addition to the effect on T cells, environmental ATO was demonstrated to affect macrophage maturation by disruption of cytoskeletal and phagocytic processes as well as deranged surface marker and cytokine expression (downregulation of CD11b, upregulation of the TLR4 coreceptor CD14, as well as of TNF-α and IL-8). , Contradicting these data, a study on inhaled ATO performed in mice demonstrated no impact on innate immune cell status, however, impaired humoral responses . Furthermore, a DC-depleting effect of As has been described in a porcine in vitro model …”
Section: Immunological Effects Of Specific Metal Drugsmentioning
confidence: 99%
“…586 Furthermore, a DCdepleting effect of As has been described in a porcine in vitro model. 587 As stated above, data on the immune impact of arsenicals are controversial, depending, among others, on the scientific focus of the studies presented or on applied doses. With regard to the therapeutic development of As compounds, a number of studies aimed to develop As compounds as immunosuppressive agents for diseases that require a reduction of immune effects such as autoimmune reactions, transplant rejection, and chronic inflammatory conditions (standing in contrast to the desired immune stimulation in anticancer therapy).…”
Section: Arsenic (As)mentioning
confidence: 99%